2018
DOI: 10.1128/mbio.02393-17
|View full text |Cite
|
Sign up to set email alerts
|

The Colibactin Genotoxin Generates DNA Interstrand Cross-Links in Infected Cells

Abstract: Colibactins are hybrid polyketide-nonribosomal peptides produced by Escherichia coli, Klebsiella pneumoniae, and other Enterobacteriaceae harboring the pks genomic island. These genotoxic metabolites are produced by pks-encoded peptide-polyketide synthases as inactive prodrugs called precolibactins, which are then converted to colibactins by deacylation for DNA-damaging effects. Colibactins are bona fide virulence factors and are suspected of promoting colorectal carcinogenesis when produced by intestinal E. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
206
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 175 publications
(237 citation statements)
references
References 58 publications
12
206
1
Order By: Relevance
“…Detection of 6 in the absence of ClbJ and ClbP indicated that ClbJ was not required for its biosynthesis. To confirm this result, we fed [1,[2][3][4][5][6][7][8][9][10][11][12][13] C2]Gly to a glycine auxotrophic BACpksΔclbP strain. We observed a +2 mass shift in the known glycine-derived precolibactin 3, but not in 6 (Figure S13), confirming that pathway A is not the source of 6.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Detection of 6 in the absence of ClbJ and ClbP indicated that ClbJ was not required for its biosynthesis. To confirm this result, we fed [1,[2][3][4][5][6][7][8][9][10][11][12][13] C2]Gly to a glycine auxotrophic BACpksΔclbP strain. We observed a +2 mass shift in the known glycine-derived precolibactin 3, but not in 6 (Figure S13), confirming that pathway A is not the source of 6.…”
Section: Resultsmentioning
confidence: 94%
“…[5][6][7] Recent studies have indicated colibactin's genotoxicity likely arises from a direct interaction with DNA, as we and others have reported the accumulation of interstrand cross-links in human cell lines incubated with pks + E. coli. [8][9] However, the underlying chemical and enzymatic basis for this activity remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…These CoPEC strains were more prevalent in most aggressive CRC tumors (TNM stage) . Colibactin is a genotoxin that induces oxidative stress and DNA double‐strand breaks in epithelial cells, leading to genomic instability . In addition to this genotoxic effect, CoPEC strains induce cellular senescence associated with the production of growth factors, such as hepatocyte growth factor, leading to an increase of tumor growth in chemically induced colitis‐associated CRC (CAC) models .…”
Section: Introductionmentioning
confidence: 99%
“…27,29 Colibactin is a genotoxin that induces oxidative stress and DNA double-strand breaks in epithelial cells, leading to genomic instability. 24,[30][31][32] In addition to this genotoxic effect, CoPEC strains induce cellular senescence associated with the production of growth factors, such as hepatocyte growth factor, leading to an increase of tumor growth in chemically induced colitis-associated CRC (CAC) models. 33 In addition, experiments using other CAC mouse models (IL-10 −/− /AOM and APC Min/+ IL10 −/− models) showed that CoPEC were able to strongly persist in the gut and to induce epithelial damage and cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…[11a,b] This is supported by arecent study showing that infection of cultured human cells with pks + bacteria results in cross-linking of genomic DNAa nd, furthermore,t hat the addition of extracellular DNAreduced this effect. [23] Healy et al recently reported that colibactin analogues featuring the unsaturated imine found in 6 only alkylated purified DNA( whilst dimethyl analogues and those representing the pyridone class of colibactins were inactive). [15a] Subsequent work using optimized assay conditions revealed that these compounds are also capable of DNAc rosslinking,h owever the adducts are more labile than those induced by pks + E. coli.…”
mentioning
confidence: 99%